STEAM-Based Learning for Mechanical Engineering - Riyadi Muslim (Universitas Sebelas Maret, 2024)
This study aims to implement the STEAM (Science Technology, Engineering Art Mathematics) based learning in the bachelor of mechanical engineering at the Universitas Sebelas Maret. Integrating STEAM learning in engineering students in design development improves students' understanding of mechanical engineering through projects, challenges, and milestones. This article focusses on how to integrate instructional project into learning-based area and evaluate how far their understanding of. In this article a descriptive approach was used. It aims to explain a phenomenon or social reality by describing variables related to a subject and unit of analysis. 33 university students studying mechanical engineering formed the study population. This study aims to provide an overview of the effectiveness of the STEAM-based learning process applied to the project design topic through descriptive research. The data indicate that learning has improved, and students are now learning more cases and actively gaining knowledge than in the past. Further details about the topic are discussed in this article.